2020
DOI: 10.1111/ajt.15763
|View full text |Cite
|
Sign up to set email alerts
|

Rejection of xenogeneic porcine islets in humanized mice is characterized by graft-infiltrating Th17 cells and activated B cells

Abstract: Xenogeneic porcine islet transplantation is a promising potential therapy for type 1 diabetes (T1D). Understanding human immune responses against porcine islets is crucial for the design of optimal immunomodulatory regimens for effective control of xenogeneic rejection of porcine islets in humans. Humanized mice are a valuable tool for studying human immune responses and therefore present an attractive alternative to human subject research. Here, by using a pig‐to‐humanized mouse model of xenogeneic islet tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…We further studied the effect of XtSCs transplantation on the immune system in vivo. Several studies have confirmed the protective role of Tregs in the modulation of immune response to xenografts, 38 whereas CD4 + IL‐17A + cells were associated with graft rejection in xenogeneic transplantation 39 . Although the in vitro model did not show any changes in these T‐cell populations, in vivo transplantation of XCs induced upregulation of CD4 + RORγt + cells, which was not observed after XtSCs transplantation, while the Treg population remained unchanged in both XtSC and XC groups.…”
Section: Discussionmentioning
confidence: 83%
“…We further studied the effect of XtSCs transplantation on the immune system in vivo. Several studies have confirmed the protective role of Tregs in the modulation of immune response to xenografts, 38 whereas CD4 + IL‐17A + cells were associated with graft rejection in xenogeneic transplantation 39 . Although the in vitro model did not show any changes in these T‐cell populations, in vivo transplantation of XCs induced upregulation of CD4 + RORγt + cells, which was not observed after XtSCs transplantation, while the Treg population remained unchanged in both XtSC and XC groups.…”
Section: Discussionmentioning
confidence: 83%
“…68 Finally, we cultured isolated islets for 6-9 days before transplantation, which is beneficial in attenuating IBMIR by reducing tissue factor content. 69 In Cohorts 1-3, the immunosuppressive regimen including rapamycin and CTLA4-Ig 70-74 plus-minus leflunomide 3,23,75 or rituximab, 20,[76][77][78][79][80] resulted in rejection that was associated with (i) expansion of circulating T cells, including TEM, granzyme B + , and IFNγ + cells CD4 + and CD8 + as well as IL-17 + CD4 + T cells, (ii) elicitation of anti-pig IgG antibodies in some recipients, (iii) dense islet infiltrates with CXCR3 + T cells and islets staining for the chemokine IP-10, and…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported prolonged xenograft survival when xenogeneic islets were transplanted into different diabetic models using cocktail immunosuppressive regimens. [46][47][48] We have recently reported the intraperitoneal administration of immunosuppressive agents comprising anti-CD19 mAb, clodronate liposomes, anti-CD154 mAb, FK, and rapamycin in pig-to-mouse islet transplantation. In this case, however, the systemic immunosuppressive regimen did not produce satisfactory outcomes, suggesting a need for more potent immunosuppression.…”
Section: Discussionmentioning
confidence: 99%